The Epidemiology of Cold-weather Injuries in Infants in Mashhad, Iran - Mohammad Saeed Sasan; Samaneh Kouzegaran; Ehsan Beykzadeh; Shahin Saeedinejat; Kolsoum Deldar; Mohammad Khajedaluee (Mashhad University of Medical Sciences, 2015)
Background: Injury is a leading cause of morbidity and mortality in children. There is insufficient data on the epidemiology or incidence of injuries in the first two years of life, especially in Iran. The main objective of this study was to describe the incidence and causes of injuries in a sample group of infants and toddlers in Mashhad, Iran. Methods: This prospective, observational study, was conducted on 1000 infants (6-24 months old), admitted to 46 healthcare centers of Mashhad. The infants were observed in terms of the occurrence of injuries and the outcomes over six months. Results: At the beginning of the study, the mean age of the infants was 13.8±7.8 months. During six months of observation, 382 episodes of injuries were detected. The injuries were burning (134 episodes), falling (132 episodes), cuts and lacerations (63 episodes), choking due to foreign body aspiration (40 episodes), poisoning (9 episodes), traffic accidents and electrical injuries (2 episodes each) and drowning (no case), respectively. During the study period, 42 injury-related outpatient visits (by a physician) were recorded, which were caused by burning (28 visits), falling (13 visits) and traffic accidents (one visit), respectively. Twenty-one cases of hospital admission were reported, although only two of them were caused by accidents (a case of falling and a case of burning). Conclusion: During the cold months, burns and falls were the main causes of injury in children, aged 6-24 months in Mashhad. However, injury was not a major cause of hospital admission in this group.